Legal Protection of Competition from Abusive Practices in the Telecommunications Sector: A Comparative Legal Study - Nasser Khalil Jalal; Serbast Qadir Hussain (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
There is no doubt that competition plays a major role in the development of trade and the national economy. Therefore, it has been of great importance in the countries that adopt the principle of free economy. This is the importance of issuing laws that regulate competition and protect them from harmful practices by banning these practices and imposing sanctions, Legal procedures, as well as the establishment of special bodies to regulate competition and prevent monopoly and protect them from such practices stipulated in those laws, for example. The importance of studying the protection of competition in the telecommunications sector and the practices violating it stems from the novelty and relatively modernity of the topic, as the unprecedented changes that the telecommunications sector witnessed at the global level date back to the last two decades of the twentieth century, It has been privatized many government institutions concerned with telecommunications networks and provide services to citizens in the majority of countries in the world, and to benefit from policies that call for liberalization of telecommunications markets and open competition and guided by the rules of the market in the provision of telecommunications services. Accordingly, in this research we have dealt with the legal protection of competition from the practices that violate it in the telecommunications sector, through comparable telecommunications laws, through two papers, in the first topic the penalties for anti-competitive practices in telecommunications laws. As for the second topic, we have devoted it to the importance of regulatory bodies for the telecommunications sector and their role in regulating competition and imposing penalties in comparative laws. Through our research, we have reached a number of conclusions and made a number of proposals.